Payment for agrobiodiversity conservation services (PACS) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The application of payment for ecosystem services (PES) specifically for agricultural biodiversity conservation. This is recognition of the value of farmers’ work in maintaining such agrobiodiversity, and the provision of positive incentives that adequately compensate them for doing so (for protecting the priority crops that are at the most risk of extinction).